Enzymatic impregnation by high hydrostatic pressure as pretreatment for the tenderization process of Chilean abalone (Concholepas concholepas). (October 2020) - Pizarro-Oteíza, Sebastián; Briones-Labarca, Vilbett; Pérez-Won, Mario; Uribe, Elsa; Lemus-Mondaca, Roberto; Cañas-Sarazúa, Raúl; Tabilo-Munizaga, Gipsy
Abstract: The aim of this study was to evaluate the effect of enzymatic impregnation by papaya latex with three different techniques (injection, immersion and high hydrostatic pressure) as a pretreatment for the tenderization process of "Chilean abalone" ( C. concholepas ). The impregnated latex activity was evaluated at 37 °C/1 h; 21 °C /6 h and 5 °C /24 h and quality parameters such as texture profile, water holding capacity, color and sensory analysis were analyzed. The results showed that high pressure pretreatment at 37 °C/1 h was the best treatment with a tenderization efficiency of 30.8%, a water holding capacity of 87.85 ± 0.25 g/100 g and a sensory evaluation of the hardness with a high correlation (r 2 = 0.927). The ranges of ΔE ranging from 5.29 to 14.50 showing how the enzymatic solutions impacted color. Finally, this research showed that the use of enzymatic impregnation improves quality parameters in comparison to the traditional mechanical tenderization. Highlights: Chilean abalone are exotic seafood products with high hardness. High pressures (HP) combined with papaya latex were applied as innovative pretreatment. Papaya latex impregnation by HP improved the tenderization process of abalone. Tenderization process of abalone affects significantly the quality parameters.